Persistence of Past-Life Memories: Study of Adults Who Claimed in Their Childhood to Remember a Past Life - HARALDSSON, ERLENDUR (Journal of Scientific Exploration, 2010)
Forty-two adults, aged 19 to 49, who claimed memories of a previous life when they were children were interviewed about their alleged memories. Over half of them had lost all these childhood memories but 38% unreservedly affirmed that they still had retained some of their past-life memories. These persons had been interviewed about their memories when they were children by Ian Stevenson or the author. The number of retained memories among those who still remembered something was about one-fifth of their original memories. The retained memories tended to center around persons they knew in their previous life and circumstances that led to their death. For half of the subjects the past-life memories had a positive impact on their life, but to some they had brought difficulties and unpleasant experiences, such as excessive attention given to them and teasing by other children. The great majority expressed general happiness with how their lives had developed. Their educational level was higher than that of their generation, as one-fourth had received some college or university education. A few of them still had phobias that they had had in their childhood and which they related to their previous life. Keywords: memory—reincarnation—longitudinal study—Sri Lanka